Ethylene Renders Silver Nanoparticles Stress Tolerance in Rice Seedlings by Regulating Endogenous Nitric Oxide Accumulation. (15th November 2022) - Tripathi, Durgesh Kumar; Kandhol, Nidhi; Rai, Padmaja; Mishra, Vipul; Pandey, Sangeeta; Deshmukh, Rupesh; Sahi, Shivendra; Sharma, Shivesh; Singh, Vijay Pratap
Abstract: Developments in the field of nanotechnology over the past few years have increased the prevalence of silver nanoparticles (AgNPs) in the environment, resulting in increased exposure of plants to AgNPs. Recently, various studies have reported the effect of AgNPs on plant growth at different concentrations. However, identifying the mechanisms and signaling molecules involved in plant responses against AgNPs stress is crucial to find an effective way to deal with the phytotoxic impacts of AgNPs on plant growth and development. Therefore, this study was envisaged to investigate the participation of ethylene in mediating the activation of AgNPs stress tolerance in rice ( Oryza sativa L.) through a switch that regulates endogenous nitric oxide (NO) accumulation. Treatment of AgNPs alone hampered the growth of rice seedlings due to severe oxidative stress as a result of decline in sulfur assimilation, glutathione (GSH) biosynthesis and alteration in the redox status of GSH. These results are also accompanied by the higher endogenous NO level. However, addition of ethephon (a donor of ethylene) reversed the AgNP-induced effects. Though the application of silicon nanoparticles (SiNPs) alone promoted the growth of rice seedlings but, interestingly their application in combination with AgNPs enhanced the AgNP-induced toxicity in the seedlings through the same routes as exhibited in the case of AgNPs alone treatment. Interestingly, addition of ethephon reversed the negative effects of SiNPs under AgNPs stress. These results suggest that ethylene might act as a switch to regulate the level of endogenous NO, which in turn could be associated with AgNPs stress tolerance in rice. Furthermore, the results also indicated that addition of l -N G -nitro arginine methyl ester (l -NAME) (an inhibitor of endogenous NO synthesis) also reversed the toxic effects of SiNPs together with AgNPs, further suggesting that the low level of endogenous NO was associated with AgNPs stress tolerance. Overall, the results indicate that the low level of endogenous NO triggers AgNPs stress tolerance, while high level leads to AgNPs toxicity by regulating sulfur assimilation, GSH biosynthesis, redox status of GSH and oxidative stress markers. The results revealed that ethylene might act as a switch for regulating AgNPs stress in rice seedlings by controlling endogenous NO accumulation.